Outstanding researchers in library science and bibliography as an object of study. Why not? - V. S. Krejdenko (Библиосфера, 2011)
An attempt is maid to remind about personality-dissertations (on researchers in library science, bibliography or bibliologist) and justify their importance for the development of our science and practice, to improve the quality of teaching, library and bibliography and bibliological disciplines. The specificity of such theses is shown, the sources of material collecting and methods of their obtaining and processing are given.